Structural Insight into IAPP‐Derived Amyloid Inhibitors and Their Mechanism of Action. Issue 14 (28th January 2020) - Niu, Zheng; Prade, Elke; Malideli, Eleni; Hille, Kathleen; Jussupow, Alexander; Mideksa, Yonatan G.; Yan, Li‐Mei; Qian, Chen; Fleisch, Markus; Messias, Ana C.; Sarkar, Riddhiman; Sattler, Michael; et al.
Abstract: Designed peptides derived from the islet amyloid polypeptide (IAPP) cross‐amyloid interaction surface with Aβ (termed interaction surface mimics or ISMs) have been shown to be highly potent inhibitors of Aβ amyloid self‐assembly. However, the molecular mechanism of their function is not well understood. Using solution‐state and solid‐state NMR spectroscopy in combination with ensemble‐averaged dynamics simulations and other biophysical methods including TEM, fluorescence spectroscopy and microscopy, and DLS, we characterize ISM structural preferences and interactions. We find that the ISM peptide R3‐GI is highly dynamic, can adopt a β‐like structure, and oligomerizes into colloid‐like assemblies in a process that is reminiscent of liquid–liquid phase separation (LLPS). Our results suggest that such assemblies yield multivalent surfaces for interactions with Aβ40. Sequestration of substrates into these colloid‐like structures provides a mechanistic basis for ISM function and the design of novel potent anti‐amyloid molecules. Abstract : ISM inhibitors are highly dynamic assemblies and exchange between monomeric and high‐molecular‐weight states. In both states, the ISM peptide adopts a β‐loop‐like structure that provides a suitable surface for sequestration of Aβ40 in the colloidal state. ISM inhibitors thus exploit multivalency by self‐association to yield high substrate avidity.